Collaboration Between Academia and Practice: Interprofessional Crises Leadership and Disaster Management. (February 2017) - Hoying, Cheryl; Farra, Sharon; Mainous, Rosalie; Baute, Rebecca; Gneuhs, Matthew
Abstract : An innovative interprofessional disaster preparedness program was designed and implemented through an academic-practice partnership between a large midwestern children's hospital and a community-based state university. This course was part of a constellation of courses developed in response to Presidential Directive (HSPD) 8, a mandate to standardize disaster response training that was issued after the inefficiencies following Hurricane Katrina. A hybrid immersive and didactic approach was used to train senior leadership and frontline clinicians. Included were simulated experiences at the National Center for Medical Readiness, a workshop, and online modules. The program that focused on crisis leadership and disaster management was developed and implemented to serve patient-centered organizations.